IMPLEMENTASI PENGENDALIAN GRATIFIKASI DAN WHISTLEBLOWING SYSTEM DALAM PEMBANGUNAN ZONA INTEGRITAS MENUJU WILAYAH BEBAS KORUPSI (Studi Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Blitar) - Wilis Asri SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The purpose of this study is to identify the implementation of gratification control and whistleblowing system in developing integrity zones for corruption-free regions. The object of this study is the Investment and One-Door Integrated Service Agency of Blitar regency. Using qualitative method, this study finds that gratification control in the development of integrity zones in the agency has been conducted by conforming with the decree of the Minister of State Apparatus and Bureaucratic Reformation number 10 of 2019. The public campaign for gratification control has been held, and the gratification control has been in effect. However, the implementation of the whistleblowing system has not conformed the aforementioned decree, where the work unit for the system has not evaluate its implementation and has not followed up the evaluation of such system. The results of this research are expected to be considered by the agency in their future policies to tackle problems in developing integrity zones for corruption-free region. Keywords: integrity zone, gratification, whistleblowing system